1996
DOI: 10.1111/j.1365-2672.1996.tb03272.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro inhibition of Helicobacter pylori by extracts of thyme

Abstract: Extracts of several plants were tested for inhibitory activity against Helicobacter pylori. Among these plants thyme (aqueous extract) and cinnamon (alcoholic extract) were the most effective. Since aqueous extract of thyme is easier to produce and consume, it was further investigated. Compared with several antibacterials, the thyme extract had a significant inhibitory effect on H. pylori, reducing both its growth and potent urease activity. From the results of this study, the aqueous extract of thyme possesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 22 publications
(8 reference statements)
1
36
0
Order By: Relevance
“…However, carvacrol constitutes less than 50% of the oil, indicating that other compounds may interact with carvacrol to confer the high level of activity to the oil. Cinnamon oil was used as a positive control, as it has already been demonstrated that the oil and its extracts are active against H. pylori (18,19).…”
Section: Disk Inhibition Assay Of H Pylori Growthmentioning
confidence: 99%
“…However, carvacrol constitutes less than 50% of the oil, indicating that other compounds may interact with carvacrol to confer the high level of activity to the oil. Cinnamon oil was used as a positive control, as it has already been demonstrated that the oil and its extracts are active against H. pylori (18,19).…”
Section: Disk Inhibition Assay Of H Pylori Growthmentioning
confidence: 99%
“…The occurrence of strains resistant to antibiotics would be expected to increase, and it is nowadays important to search for nonantibiotic substances with anti-H. pylori activity. Herbal extracts and essential oils have been used as traditional medicines for thousands of years all over the world, and their anti-H. pylori activity has been widely demonstrated in vitro (2)(3)(4)(5). Many foodstuffs have also exhibited inhibitory activity against the growth of H. pylori in vitro, among others, red wine (6,7), sprouted peas (8), green tea (9), and cranberry juice (10).…”
Section: Introductionmentioning
confidence: 99%
“…A wide spectrum of pharmacological activities have been described for thyme, such as antioxidant (13), antibacterial (26,27) and antifungal (28,29) properties. These activities have been attributed to some widely distributed species of thyme.…”
Section: Discussionmentioning
confidence: 99%